Probiotic inhibits oral carcinogenesis: A systematic review and meta-analysis - Wan Mohd Kamaluddin, Wan Nur Fatihah; Rismayuddin, Nurul Alia Risma; Ismail, Ahmad Faisal; Mohamad Aidid, Edre; Othman, Noratikah; Mohamad, Noor Afifah Hanin; Arzmi, Mohd Hafiz (Elsevier, 2020)
Objectives: This systematic review aimed to investigate the effects if probiotics can inhibit oral carcinogenesis. Design: PubMed, Web of Science, Scopus, and PLOS databases were searched up to February 2020 to identify randomised controlled trials that fulfilled the eligibility criteria. Joanna Briggs Institute (JBI) Critical Appraisal Tool was used for quality assessment of articles. This review was performed according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA-P) 2015 protocol guidelines. Result: The initial search retrieved 774 articles. Of these, only five articles were included in the qualitative synthesis. Two out of the five papers were further analysed for quantitative synthesis in meta-analysis. The majority of the included studies were found to be of “moderate quality”. The qualitative synthesis found four probiotics that exhibited potential therapeutic effects in oral carcinogenesis, includingAcetobacter syzygii, AJ2, Lactobacillus plantarum, and Lactobacillus salivarius REN. Among them, the application of L. salivarius REN re- sulted in a 95 % lower risk for developing oral cancer (p < 0.05). Conclusion: It is known that probiotics have the potential to inhibit oral carcinogenesis, thus supporting the hypothesis of the study. The ability of L. salivarius REN to inhibit the development of oral cancer suggested that this bacterium can be a potential inhibitory agent against oral carcinogenesis.